Synthesis, characterization and fluorescence properties of selected pyrazine derivatives / Hasna Nadiah Binti Johari - Johari, Hasna Nadiah (2015)

(untitled)
Phenoxypyrazine (44), 2-o-methylphenoxypyrazine (46), 2-m-methylphenoxypyrazine (48), 2-p-methylphenoxypyrazine (50) and 2-N-piperidinopyrazine (56) were obtained after the reaction between 2-chloropyrazine (42) with phenol (43), o-cresol (45), m-cresol (47), p-cresol (49) and piperidine (55) respectively. 5-Phenoxypyrazine-2-carboxylic acid methyl ester (58), 5-m-tolyloxypyrazine-2-carboxylic acid methyl ester (59), 5-(-3-nitrophenoxy)pyrazine-2-carboxilic acid methyl ester (61) on the other hand, were obtained after the reaction between 2-chloropyrazine-5-carboxylic acid methyl ester (57) with phenol (43), 3-methylphenol (47), and 3-nitrophenol (60) respectively. While, 2,5-dimethyl-3 phenoxypyrazine (63) were prepared by reacting 3-chloro-2,5-dimethyl pyrazine (62) with phenol (43). Naphthalenyloxy pyrazine derivatives, 2-naphthalen-1-yloxypyrazine (52), and 2-naphthalen-2-yloxypyrazine (54) were prepared by reacting 2-chloropyrazine (42) with 1-naphtol (51) and 2-naphtol (53) respectively. The structures of these compounds were confirmed using 1H NMR, 13CNMR, GC-MS and IR spectra. The fluorescence properties were recorded using Luminescence Spectrophotometer. Fluorescence characteristic of phenoxy pyrazine derivatives studied showed fluorescence intensity varies with concentration. Compound (46), (50) and (63) showed fluorescence quenched in the presence of oxygen. Besides, compound (44) and (61) showed higher fluorescence intensity in alkaline condition. Furthermore, compound (46), (50) and (63) exhibit highest emission in nonpolar solvents and drastic fall in fluorescence emission in polar aprotic solvents. Highest fluorescence intensity were observed by phenoxy pyrazine derivatives with electron donating group nature, and subtituent at ortho and para position in benzene ring whereas, naphthalenyloxy pyrazine derivatives with linear and rigid structure showed highest fluorescence intensity.